Pembentukan Karakter Melalui Moderal Makanan Sehat dan Kebersihan Diri Bagi SDN Trebungan Bondowoso - Akmal Firdautillah; Intania Kirani Hasanah; Muhammad Raihan Akbar; Nindy Varissa Zalianty Putri; Tia Amalia Putri Yuristina; Windy Dwi Magfiroh; Yolanda Aghniatul Maghfiro; Susan Barbara Patricia Sembiring Meliala; Agung Nugroho Puspito (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2026)
The implementation of clean and healthy living practices should begin at the elementary education level, as children are in a critical period of character and habit development that will influence their future lives. Healthy habits instilled from an early age play a vital role in supporting children's physical and mental development while preventing various health problems later in life. However, many elementary school children remain unaware of the importance of consuming nutritious food and maintaining personal hygiene, putting them at risk of health and nutritional problems. Therefore, effective and sustainable health education efforts are needed to increase students' knowledge and awareness. The program was designed to enhance understanding and attitudes toward clean and healthy living among elementary school students through engaging, enjoyable, and age-appropriate learning methods. The approach included outreach and counseling using various educational media, such as slide presentations, educational videos, and interactive games that encouraged active student participation. Evaluations were conducted before and after the activities to measure changes in students' knowledge and behavior. The program was implemented at Trebungan Elementary School, Bondowoso Regency, in three sessions involving 20 second-grade students. The evaluation results showed an increase in students' knowledge about healthy food, from 77.8% in the pre-test to 99.8% in the post-test. Additionally, the percentage of students able to wash their hands correctly also increased significantly, from 16.7% before the activity to 88.9% after the program. These findings demonstrate that the socialization of clean and healthy living behaviors is effective in increasing understanding and developing clean and healthy living habits among elementary school students, thus having the potential to support the creation of a healthy and conducive school environment.